2020
DOI: 10.2169/internalmedicine.3633-19
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Colitis Followed by Colonic Pseudolipomatosis and Gastric Emphysema in a Post-resuscitation Patient

Abstract: A 64-year-old Japanese man suffered cardiopulmonary arrest, which may have resulted from sepsis and/or hyperosmolar hyperglycemic non-ketonic coma, and was admitted after successful resuscitation. He had watery diarrhea on day 18 and was diagnosed with cytomegalovirus enterocolitis. In addition, computed tomography performed on day 27 and colonoscopy revealed gastric emphysema and intestinal pseudolipomatosis, respectively. This report is the first to describe a patient with cytomegalovirus enterocolitis and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…It has been suggested that pseudolipomatosis may be caused by intestinal bacteria releasing gas [ 11 , 17 ]. Iwamuro et al reported a case of a patient presenting with colonic pseudolipomatosis following cytomegalovirus colitis [ 23 ]. Cases of gastric pseudolipomatosis have also been described and connected to Helicobacter pylori infection [ 8 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that pseudolipomatosis may be caused by intestinal bacteria releasing gas [ 11 , 17 ]. Iwamuro et al reported a case of a patient presenting with colonic pseudolipomatosis following cytomegalovirus colitis [ 23 ]. Cases of gastric pseudolipomatosis have also been described and connected to Helicobacter pylori infection [ 8 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal wall thickening was observed in 20.0% of patients in this study. As colonoscopy was not performed in all patients except for one patient with cytomegalovirus colitis 7 , leaving many aspects regarding the causes of colorectal wall thickening in gastric emphysema and the relationship between the two conditions unclear. Further accumulation of cases is required for a better understanding of this feature.…”
Section: Discussionmentioning
confidence: 99%
“…3A, arrowhead). A subset of the patients examined (5/46) also participated in our previous studies [6][7][8][9] . We conducted a retrospective chart review of the patients' age, sex, underlying diseases, presence or absence of portal venous gas, presence or absence of colorectal wall thickening, treatment, and outcomes.…”
Section: Methodsmentioning
confidence: 99%